Perceived Effectiveness of Indigenous Technical Knowledge (ITK) in Modern Agriculture in Haryana State (Indian Journal of Extension Education, 2020)
India is a country of many aboriginal communities, with unique traditional knowledge. These traditional knowledge and technologies have played a significant role in the development of the communities. To find out the perception of the modern farmers about the value and effectiveness of the ITKs in today’s agriculture a study was carried out in two districts Haryana state namely, Karnal and Sirsa by interviewing 60 farmers from each district. It was observed that the use of compost, neem leaves, biogas slurry and ash were ranked at top as they were perceived to be very effective and popular methods of ITK. The use of egg shells bone meal, crop rotation, use of alcohol, growing pest repelling plants, dhatura, chilli, cowpathy, use of barriers and traps, growing only native plants, talex of aak, tobacco, kerosene oil and garlic followed in series. Other ITKs like use of canola oil, amritpani, castor oil, engine oil, soap, karanj seeds, buttermilk, garlic, limonene and vinegar were not known by the farmers. This indicates that the modern farmers didn’t much rely on the ITKs due to the availability of chemical fertilizers and pesticides in market and also because there is lack of awareness among them about certain ITKs thus, there is an urgent need of documenting and preserving the Indigenous Technical Knowledge, many of which are at the edge of extinction. There is also lack of proper links between the practice of indigenous and modern knowledge and technologies which can be a reason for the losing faith of modern farmers in their traditional knowledge.